2012
DOI: 10.1002/tesq.6
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Writers’ Strategy Use and Performance on an Integrated Reading‐Listening‐Writing Task

Abstract: Integrated writing tasks that involve different language modalities such as reading and listening have increasingly been used as means to assess academic writing. Thus, there is a need for understanding how test-takers coordinate different skills to complete these tasks. This study explored second language writers' strategy use and its relationship to test performance on an integrated reading-listeningwriting test task using a structural equation modeling approach. The results reveal that integrated writing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 60 publications
8
58
1
4
Order By: Relevance
“…This finding is supported by a large number of studies conducted previously (Cesur 2011, Dreyer & Oxford 1996, Yang & Plakans 2012. Therefore, using learning strategies should be encouraged in L2 classes.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…This finding is supported by a large number of studies conducted previously (Cesur 2011, Dreyer & Oxford 1996, Yang & Plakans 2012. Therefore, using learning strategies should be encouraged in L2 classes.…”
Section: Resultssupporting
confidence: 60%
“…Using learning strategies influences how well students learn another language and helps to promote language achievement (Hsaio & Oxford 2002). In their studies on the effect of language learning strategy use on students' English achievement, Cesur (2011), Dreyer and Oxford (1996) and Yang and Plakans (2012) concluded that compared with less proficient students, more proficient ones utilised more learning strategies. Hence, it is hypothesised in this study that strategy use has a direct effect on English achievement.…”
Section: Language Learning Strategiesmentioning
confidence: 99%
“…Among these skills, paraphrasing is commonly quite difficult for EFL learners, although it has received little attention as a research topic. L2 summary writing has been investigated from various perspectives, such as by examining the use of strategies (Johns, 1985), the role of constructs (Asención-Delaney, 2008;Baba, 2009), composition processes (Plakans, 2008), and the relationship between strategy use and the end product in summary writing (Yang & Plakans, 2012). Some empirical studies have also been published that address paraphrasing among NNESs (e.g., Keck, 2006Keck, , 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…test takers tend to demonstrate high-level cognitive processes, such as reformulating and reproducing information (Frost, Elder & Wigglesworth, 2012), and other regulation skills for managing reading, listening, and writing interactions (Yang & Plakans, 2012). In investigating the two types of computerized PTE Academic integrative skills tasks, Rukthong and Brunfaut (2015) also found that their participants had reported more 'lower-level processes' (input decoding and syntactic parsing) than 'higher-level processes' (such as structural building and integrating/linking pieces of information).…”
Section: Discussionmentioning
confidence: 99%